Delivering functionality in foods : from structure design to product engineering / António Vicente, Cristina Silva, Chelo Gonzalez, editors. - Vicente, António A.; Silva, Cristina; Gonzalez, Chelo (Springer, 2022)
This singular text aims to strengthen the scientific understanding of food product design and engineering, and to stimulate and accelerate the development of innovative, complex and highly structured products and suitable production processes. By gathering an interdisciplinary team of scientists from the research areas of food engineering, biophysics, applied soft matter, food technology and applied human nutrition, this book contributes to an integrated process and product design approach for creating innovative, multi-phase structured foods delivering functionality. Delivering functionality in foods: from structure design to product engineering serves as an important reference for food engineers, food technologists and nutritionists, covering all aspects of the design of food structures and their application in the development of functional food products. From the delivery of health-related functionalities to process and product engineering for delivery of multiple food properties, this work provides a comprehensive overview of the knowledge, processes and technologies required for the design of functional foods.
Includes index.
Keywords: Food -- Biotechnology.; Food -- Composition.; Food science.